Retrospective Analysis of Advanced Maternal Age Pregnancies - Aslı Göker Tamay; Tevfik Güvenal; Nazan Özgür; Semra Oruç Koltan; Faik Mümtaz Koyuncu (Medical Network, 2011)
OBJECTIVE: To evaluate maternal and fetal outcome in pregnancies of women aged 35 and more. STUDY DESIGN: In this retrospective analysis of advanced maternal age pregnancies a total of 237 patient records were evaluated. Age, gestational age, birth weights, Apgar scores, maternal hemoglobin, hematocrit, preeclampsia, cesarean section, gestational diabetes, intrauterine fetal demise and fetal anomalies were compared between young and older women. RESULTS: There was a higher rate of preeclampsia, gestational diabetes and intrauterine fetal demise in the older age group. Higher 5th minute Apgar scores, higher hematocrit values and higher cesarean section rates were observed in the control age group. There was no difference in terms of birth weight, prematurity, low birth weight, meconium aspiration or fetal anomaly. CONCLUSION: Advanced maternal age is a risk factor for preeclampsia and gestational diabetes even in healthy women. Meticulous antenatal care should be offered to older pregnant women for the prevention of maternal complications.